Intussusception in pregnancy after gastric bypass: a case report. Issue 6 (1st November 2016) - Mortelmans, D.; Mannaerts, D.; Van den Broeck, S.; Jacquemyn, Y.; Hubens, G.
Abstract: Laparoscopic Roux-en-Y gastric bypass (RYGB) remains the gold standard procedure in obesity surgery and is mostly performed in young women of reproductive age. Since the worldwide prevalence of obesity is increasing and fertility improves after surgery, more complications in the pregnant population will emerge. The differential diagnosis of acute abdominal pain in patients with a history of gastric bypass is rather broad and includes mainly anastomotic ulcers, leaks, and small bowel obstructions. Early diagnosis and treatment of these complications is of utmost importance and should be performed on a multidisciplinary basis. Whether surgery should be performed by laparoscopy or laparotomy remains subject of discussion. We report a case of a 29-year-old pregnant woman at 33 + 5 weeks gestational age, presenting with an intussusception after RYGB. A successful surgical reduction was performed by laparotomy.